Effectiveness of recombinant hepatitis B vaccine with/without the passive hepatitis B immunoglobulin vaccine in babies whose mothers are hepatitis B surface antigen positive in a private missionary hospital - Abiodun, Olusanya; Onibonoje, Omobolaji; Ola, Oluwadara; Ishola, Sophie (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Hepatitis B infection is a potentially life-threatening liver infection. The burden is more in the less developed countries. Vaccination is the most cost-effective way to control hepatitis B virus (HBV) infection and its chronic complications globally. Active-passive immunoprophylaxis using hepatitis B immunoglobulin combined with recombinant hepatitis B vaccine is recommended for infants of women with chronic HBV infection. This study aimed to determine the effectiveness of the hepatitis B recombinant vaccine alone or combined with hepatitis B immunoglobulin. Methods: The study was a prospective longitudinal study. Patients were selected using a convenient sampling technique. The study spanned between 1 January 2017 and 31 December 2018. Data analysis was with SPSS version 21. Results: The unit recorded 1690 deliveries during the recruitment period, 70 eligible patients were recruited thus giving an incidence of 4.1%. 74.3% of the recruited patients were HBeAg negative while 25.7% were HBeAg positive. 52.9% of the babies had only recombinant HB recombinant vaccine while 47.1% had combined hepatitis B immunoglobulin and the recombinant vaccine at birth. The HBeAg status of mothers played a significant factor in the HBsAg positivity of babies two months after the completion of immunoprophylaxis against HBV. Conclusions: Giving recombinant HBV vaccine in combination with the HBV immunoglobulin is the standard practice, this may not always be so based on the findings from this study. However, the population studied is too small to make a categorical statement thus a larger population needs to be studied.